Implementation of Geragogy-Based Complementary Acupressure Therapy to Improve Independence Among Elderly Individuals with Gout - Popy Irawati; Roswita R; Nopi Suci (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Gout is an inflammatory joint disease commonly experienced by older adults, causing chronic pain and limitations in mobility. Non-pharmacological approaches such as acupressure can serve as a safe and easy complementary therapy that can be performed independently. Health education for older adults requires a specific approach that considers cognitive, sensory, and psychosocial aspects. The gerontological education model (Geragogy) is a learning approach designed according to the characteristics of older adults, using slow-paced delivery, repetition, clear visual aids, and direct practice. This community service activity aimed to improve the knowledge and skills of older adults in performing acupressure to reduce gout complaints. The program was conducted in Neglasari District, Tangerang City, through interactive lectures, demonstrations, repeated practice, and individual assistance. Evaluation was carried out using pre- and post-tests as well as skills observation. The results showed an increase in knowledge from low to moderate and high categories, and most participants were able to perform acupressure independently. These findings indicate that the geragogy-based approach is an effective initial step for providing sustainable health education for older adults.